Novel Diagnostic Autoantibodies in Rheumatoid Arthritis - Burcu Yanık; Duygu Geler Külcü (Archives of Rheumatology, 2008)
Early diagnosis and early treatment can prevent joint damage in rheumatoid arthritis (RA); but the lack of appropriate diagnostic criteria hinders early diagnosis. There are not many disease-specific serological markers for the diagnosis of the disease. Highly sensitive and specific markers are needed in the early stages of the disease. The autoantibodies which probably play an importanat role in the pathogenesis of RA and have increasingly been examined in recent years, will be reviewed, discussed, and examples given of the work done. (Romatizma 2008; 23: 97-9)